2014
DOI: 10.1007/s40684-014-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model-based evaluation methodology for environmental burden of chemical mechanical planarization process

Abstract: Chemical mechanical planarization (CMP) is an essential manufacturing process in semiconductor fabrication. Chipmakers continue to adopt CMP for device planarization or surface finishing of substrate materials. Evaluating the environmental impact of the CMP process may contribute to the greening of the semiconductor process. In this paper, we propose a mathematical model-based evaluation method to determine the environmental burden of the CMP process. We adopted our previously reported material removal rate (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Lee et al [27] proposed a mathematical model-based evaluation methodology to develop a CMP model based on the mechanical contact [28] and kinematic models [29,30] for analyzing the environmental burden caused by CMP. They classified the consumables in the CMP as long lifespan CMP countable and short lifespan CMP countable and defined them as follows.…”
Section: Fig 3 Schematic Of Materials and Energy Flow For Cmp And Cmp Consumablementioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [27] proposed a mathematical model-based evaluation methodology to develop a CMP model based on the mechanical contact [28] and kinematic models [29,30] for analyzing the environmental burden caused by CMP. They classified the consumables in the CMP as long lifespan CMP countable and short lifespan CMP countable and defined them as follows.…”
Section: Fig 3 Schematic Of Materials and Energy Flow For Cmp And Cmp Consumablementioning
confidence: 99%
“…Lee et al [27] proposed the environmental burden assessment method to obtain the process time required to remove the targeted film thickness through the MRR model. Then, the electrical energy consumption, slurry consumption, and UPW consumption during the process time are calculated and converted to CDE (Fig.…”
Section: Fig 3 Schematic Of Materials and Energy Flow For Cmp And Cmp Consumablementioning
confidence: 99%
“…This manufacturing involves the development of products through processes that are environmentally friendly, energy and resources efficient. Sustainable manufacturing has been defined as development of products via processes with optimal energy and natural resources conservation, and minimal negative environmental consequences for employees, communities, and consumers ( Ball et al., 2009 ; Branker et al., 2011 ; Loglisci et al., 2013 ; Lee et al., 2014 ; Yi et al., 2015 ; Gupta et al., 2016 ; Li et al., 2017 ). The quest to develop smart products which will meet functional requirements using emerging materials within a short manufacturing cycle time has led to increase in energy requirement of the manufacturing processes with environmental impact and cost consequences ( Priarone, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…They adopt our previously reported material removal rate model for CMP and modified it to incorporate the effect of the slurry flow rate and process temperature. The results showed that slurry consumption strongly impacts the carbon dioxide equivalents of the CMP process [9]. Yang et al proposed a chip-scale CMP model that is based on the Greenwood-Williamson theory.…”
Section: Introductionmentioning
confidence: 99%